TEACHING GENDER TERMINOLOGY, EFFECTIVE TEACHING STRATEGIES OF TEACHING GENDER TERMINOLOGY, RESOURCES AND CHALLENGES OF TEACHING TERMINOLOGY IN AN ESL CLASSROOM (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article highlights gender terminology and effective teaching methods, sources and problems of teaching gender terminology in English as a second foreign language classes